Synthesis, Crystal Structures And Photoluminescence Studies Of Metal Complexes Containing Ligands Derived From Diels-Alder Adduct - Azmi, Nurul Izzati (2021)
A condensation reaction between the Diels-Alder adducts of anthracene and maleic anhydride with